Art and the Periphery and Foteini Vlachou: Exploring the "Difference Within" in European and Western Art. (2nd October 2019) - Pezzini, Barbara
Abstract : This special issue of Visual Resources builds upon the research of Foteini Vlachou (1975–2017). Vlachou intended to be Art and the Periphery 's Guest Editor, but the project was tragically interrupted by her death and this volume is now published in memoriam . Even if recent studies on the periphery have focused principally on the Global South, Art and the Periphery follows Vlachou's take on the subject, exploring principally how the concept of periphery developed within the European and Western tradition. This issue, therefore, brings together case studies on ancient Egyptian art, Latin American artists in Paris, Iberian modernism, the internationalization of French Surrealism, museums in the Austro-Hungarian Empire, and Norwegian architecture. The articles assume, as advocated by Vlachou in her unfinished contribution in this volume, a wide range of methodological and theoretical positions, while maintaining a strong awareness of the periphery's political association with capitalism and its fundamentally unequal power configurations. This introduction presents the contributions of the special issue in the context of Vlachou's own work and interprets them through the lens of postcolonial theory, especially taking heed of the observations by cultural theorist Homi Bhabha (b. 1949) on the transmission of European cultural mechanisms and their reflection into global inequalities. A final coda identifies the study of art and the periphery as particularly relevant for Europe in this historical moment in which its unity is questioned by many of its nations.